2001
DOI: 10.1016/s0008-6363(01)00404-7
|View full text |Cite
|
Sign up to set email alerts
|

Sustained retention of tetradecylthioacetic acid after local delivery reduces angioplasty-induced coronary stenosis in the minipig

Abstract: Local delivery of TTA reduces coronary artery stenosis after PTCA as assessed by both angiographic, histomorphometric and ICUS examinations by influencing vessel remodeling rather than intimal hyperplasia. The underlying mechanism(s) seem to involve antioxidant and anti-inflammatory effects of this fatty acid analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Indeed, we found a significant 98% increased transcription of IL10 . Hence, indicating that TTA increases expression of IL10 in poly(I:C) activated macrophages, similar to the effects reported from human PBMCs stimulated with TTA [49,50]. …”
Section: Discussionsupporting
confidence: 84%
“…Indeed, we found a significant 98% increased transcription of IL10 . Hence, indicating that TTA increases expression of IL10 in poly(I:C) activated macrophages, similar to the effects reported from human PBMCs stimulated with TTA [49,50]. …”
Section: Discussionsupporting
confidence: 84%
“…37 We have previously shown that TTA reduces restenosis in pigs. 37 Selenium is a stronger reducing agent than sulfur, and our data indicate that TSA may reduce the degree of coronary artery intimal thickening in pigs undergoing PCI.…”
Section: Discussionmentioning
confidence: 95%
“…37 We have previously shown that TTA reduces restenosis in pigs. 37 Selenium is a stronger reducing agent than sulfur, and our data indicate that TSA may reduce the degree of coronary artery intimal thickening in pigs undergoing PCI. These findings suggest that the antioxidant, antiinflammatory, and hypolipidemic properties of TSA may not merely be an in vitro phenomenon, but could induce antiproliferative effects after PCI in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…TTA inhibits proliferation of smooth muscle cells and has the ability to attenuate TNFα-mediated endothelial cell activity involving both PPARα-dependent and –independent pathways [16]. As previously reported, TTA was taken up in the arterial wall [18]. Thus, its anti-atherosclerotic effect could be a direct action on the vascular cells with anti-inflammatory and antioxidative effects, at least partly related to its effect of the local fatty acid composition.…”
Section: Discussionmentioning
confidence: 97%
“…The anti-inflammatory effects of TTA appear to involve both PPARα-dependent and –independent pathways [16]. Finally, TTA is found to be present in the coronary wall [18], suggesting a potential for a direct effect on coronary atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%